Assessment of a Siloxane Poly(urethane‐urea) Elastomer Designed for Implantable Heart Valve Leaflets. Issue 2 (21st December 2020) - Jenney, Chris; Millson, Peter; Grainger, David W.; Grubbs, Robert; Gunatillake, Pathiraja; McCarthy, Simon J.; Runt, James; Beith, Jason
Abstract : Synthetic polymer leaflets in prosthetic cardiac valves hold the potential to reduce calcification and thrombus, while improving blood flow, durability, and device economics. A recently developed siloxane poly(urethane‐urea) (LifePolymer, LP) exhibits properties essential for heart valve leaflets, including low dynamic modulus, high tensile strength, minimal creep, and excellent biostability. LP's properties result from carefully designed "linked co‐macrodiol" chemistry that maximizes silicone content and virtual crosslinks between soft and hard phases. Characterization of multiple commercial batches demonstrates a robust synthesis process with minimal variation. Extensive ISO 10993–based biocompatibility testing results in no observable toxicity or other adverse reactions. An ex vivo AV shunt thrombogenicity investigation reveals nearly undetectable levels of platelet attachment and thrombus formation on LP surfaces. Chronic ovine implantation of prototype heart valves with LP leaflets shows no differences in thrombogenicity or systemic tissue response when compared to a clinically standard tissue‐based valve. Toxicological risk assessment, based on extractables and leachables analysis of LP‐based heart valves, confirms minimal toxicological risk. Lastly, 24‐week, strain‐accelerated in vivo LP biostability testing confirms previous favorable in vitro biostability findings. These studies demonstrate that this newly developed elastomer exhibits ideal biomaterial properties for the flexible leaflets of a totally synthetic heart valve replacement. Abstract : A siloxane poly(urethane‐urea) elastomer recently developed for heart valve leaflets demonstrates a robust, scalable synthesis process with minimal variation. Aggressive testing confirms biocompatibility, negligible toxicological risk from extractable and leachable compounds, low thrombogenicity, and excellent biostability. Ovine implantation of heart valves integrating this new elastomer confirms leaflet function and tissue/blood compatibility.